Konseling Pastoral Kristen bagi Jemaat yang Mengalami Trauma akibat Penolakan Sosial (Pusat Riset dan Inovasi Nasional, 2024)
This article constructs a Christian pastoral counseling framework for congregants who experience trauma caused by social rejection. Social rejection within family, peer, workplace, or church communities may wound identity, belonging, agency, and spiritual meaning; however, pastoral responses often remain either overly moralistic or merely consolatory. The objective of this study is to formulate a trauma-informed and theologically accountable model of pastoral counseling that can be used by local church ministers without replacing professional mental health care. This study uses a qualitative constructive literature review by synthesizing recent studies on trauma-informed care, social exclusion, religious coping, chaplaincy, and pastoral theology published before 2024. The analysis identifies five core findings: trauma from social rejection is primarily relational; pastoral care must begin with safety, consent, and validation; theological interpretation should resist victim-blaming; congregational belonging is part of recovery; and referral ethics are necessary when symptoms exceed pastoral competence. The proposed model integrates safe presence, narrative listening, theological reconstruction, communal restoration, and clinical referral. The implication is that churches need a pastoral counseling culture that protects wounded congregants from retraumatization while sustaining spiritual hope, relational repair, and responsible interdisciplinary collaboration.